EIF4A inhibition targets bioenergetic homeostasis in AML MOLM-14 cells in vitro and in vivo and synergizes with cytarabine and venetoclax - Katie Fooks; Gabriela Galicia-Vazquez; Victor Gife; Alejandro Schcolnik-Cabrera; Zaynab Nouhi; William W. L. Poon; Vincent Luo; Ryan N. Rys; Raquel Aloyz; Alexandre Orthwein; Nathalie A. Johnson; Laura Hulea; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background Acute myeloid leukemia (AML) is an aggressive hematological cancer resulting from uncontrolled proliferation of differentiation-blocked myeloid cells. Seventy percent of AML patients are currently not cured with available treatments, highlighting the need of novel therapeutic strategies. A promising target in AML is the mammalian target of rapamycin complex 1 (mTORC1). Clinical inhibition of mTORC1 is limited by its reactivation through compensatory and regulatory feedback loops. Here, we explored a strategy to curtail these drawbacks through inhibition of an important effector of the mTORC1signaling pathway, the eukaryotic initiation factor 4A (eIF4A). Methods We tested the anti-leukemic effect of a potent and specific eIF4A inhibitor (eIF4Ai), CR-1-31-B, in combination with cytosine arabinoside (araC) or the BCL2 inhibitor venetoclax. We utilized the MOLM-14 human AML cell line to model chemoresistant disease both in vitro and in vivo. In eIF4Ai-treated cells, we assessed for changes in survival, apoptotic priming, de novo protein synthesis, targeted intracellular metabolite content, bioenergetic profile, mitochondrial reactive oxygen species (mtROS) and mitochondrial membrane potential (MMP). Results eIF4Ai exhibits anti-leukemia activity in vivo while sparing non-malignant myeloid cells. In vitro, eIF4Ai synergizes with two therapeutic agents in AML, araC and venetoclax. EIF4Ai reduces mitochondrial membrane potential (MMP) and the rate of ATP synthesis from mitochondrial respiration and glycolysis. Furthermore, eIF4i enhanced apoptotic priming while reducing the expression levels of the antiapoptotic factors BCL2, BCL-XL and MCL1. Concomitantly, eIF4Ai decreases intracellular levels of specific metabolic intermediates of the tricarboxylic acid cycle (TCA cycle) and glucose metabolism, while enhancing mtROS. In vitro redox stress contributes to eIF4Ai cytotoxicity, as treatment with a ROS scavenger partially rescued the viability of eIF4A inhibition. Conclusions We discovered that chemoresistant MOLM-14 cells rely on eIF4A-dependent cap translation for survival in vitro and in vivo. EIF4A drives an intrinsic metabolic program sustaining bioenergetic and redox homeostasis and regulates the expression of anti-apoptotic proteins. Overall, our work suggests that eIF4A-dependent cap translation contributes to adaptive processes involved in resistance to relevant therapeutic agents in AML.